TEACHER DEVELOPMENT MODEL TOWARDS ACTIVE LEARNING, INTEGRATING THE PHILOSOPHY OF SUFFICIENCY ECONOMY FOR SCHOOLS UNDER PHUKET PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Hinnoi, Chanyapak; Raksatham, Sompong; Chatakan, Weerayut (Journal of MCU Nakhondhat, 2026)
The research aimed to 1) study the teacher development process towards active learning integrating the philosophy of sufficiency economy for educational institutions, 2) create a model for teacher development towards active learning integrating the philosophy of sufficiency economy for educational institutions, and 3) validate the model for teacher development towards active learning integrating the philosophy of sufficiency economy for educational institutions. The research employed a mixed-methods approach in three phases: Phase 1 involved a sample of 266 teachers from the Phuket Primary Educational Service Area Office, with 15 key informants. The tools used were questionnaires and interviews. Statistical analysis included frequency, percentage, mean, and standard deviation. Phase 2 involved drafting the teacher development model. Phase 3 involved expert-based seminars with 9 participants and focus group discussions with 9 participants. Content analysis was used to analyze the findings. The research results showed that 1) The teacher development process towards active learning integrating the philosophy of sufficiency economy consists of 5 steps: curriculum design, teacher development implementation, supervision and monitoring of teacher development, evaluation and reflection, and improvement and development. 2) The model for teacher development towards active learning integrating the philosophy of sufficiency economy in educational institutions consists of 5 components: the name of the model, the principles of the model, the objectives of the model, the methods of implementation of the model, and the conditions for success. 3) The results of the assessment of the suitability, feasibility, accuracy, and usefulness of the teacher development model for active learning integrating the philosophy of sufficiency economy for educational institutions had the highest average score in all aspects.